Pengaruh Penggunaan Plastik LDPE (Low Density Polyethylene) Sebagai Substitusi Aspal dan Serbuk Kaca Sebagai Substitusi Filler pada Campuran LASTON AC-WC - Ageng Surya Adjie; Alif Nur Rizqi; Riza Susanti; Asri Nurdiana (Universitas Diponegoro, 2024)
Road deterioration is a common problem in Indonesia, influenced by population growth, the number of vehicles, and environmental factors. LASTON (Asphalt Concrete Layer) is a type of flexible pavement consisting of a mixture of asphalt, aggregate, and filler, which requires innovation to improve its quality. The objectives of this study were to determine the marshall parameters of LASTON AC-WC mixtures added with LDPE plastic and glass powder variations, obtain the KAO (Optimum Asphalt Content) value, and find the price efficiency of Conventional LASTON AC-WC mixtures and Innovative LASTON AC-WC. The research method used was an experimental test at the Civil Engineering Laboratory of Diponegoro University Vocational School, referring to the 2018 Bina Marga standard (Revision 2). This study designed 15 samples to obtain the KAO value so that the KAO obtained from the marshall test calculation was 5.5%, as well as 27 samples to determine the optimum content of LDPE plastic and Glass Powder with variations in LDPE plastic content of 4%, 5%, and 6% by weight of asphalt and Glass Powder content of 25%, 50%, and 75% by weight of fillers. The variations were tested using hot asphalt mixtures' stability and flow test methods with marshall test equipment referring to the 2018 General Specifications. This study obtained the optimum percentage of LDPE 5% and Glass Powder 75%, which met the requirements of the 2018 General Specifications. The marshall test results show the BJ Bulk value of 2.399 T/m3, VIM 4.901%, VMA 14.063%, VFA 70.393%, Stability 2029.455 kg, Flow 2.297 mm, and MQ 868.783 kg/mm. The cost of conventional asphalt mixture material is Rp 1,046,123, while the cost of innovative asphalt mixture material is Rp 987,017; thus, the innovative asphalt mixture material is more economical, with a price difference of Rp 59,105.90/ton.